Investigation of the interactions among preschool teachers’ components of pedagogical content knowledge for early science teaching - Kutluca, Ali Yiğit (Southeast Asia Early Childhood Journal, 2021)
The purpose of this case study is to explore the pedagogical constructions of preschool teachers towards science teaching and the interactions between pedagogical content knowledge (PCK) components. PCK Mapping, which is a pictorial methodological approach, has been used to reach this purpose. The case addressed in this study is to understand the nature of the interaction between the PCK components that preschool teachers use while planning and implementing the yoghurt-making activity. In order to better understand this case, six preschool teachers from different experiences participated in the study. This design is a multiple case study as the PCK conceptualization of each participant represents a different case. The data in the study were collected through Content Representations (CoRes) and Instruction Based Interviews. All participants first planned a science teaching activity (making yoghurt) through CoRes, then answered questions about their teaching background, science teaching orientations and the activity. Afterwards, interviews were made about the pedagogical tools they used while structuring the teaching. Finally, each teacher was observed and videotaped while teaching the yoghurt-making activity. After the observations, Video-Stimulated Recall interviews were made with them. Data were analysed through in-depth analysis of explicit PCK, enumerative approach, PCK mapping and the constant comparative method. The results show that preschool teachers use children’s cognitive potentials, teaching strategies, and epistemological and pedagogical orientations while planning and implementing science teaching and they frequently associate them. In addition, preschool teachers have a lack of linking curriculum materials with science teaching and other PCK components.